A Directional Crack Damage Memory Effect in Sandstone Under True Triaxial Loading. Issue 14 (20th July 2018) - Browning, John; Meredith, Philip G.; Stuart, Christopher; Harland, Sophie; Healy, David; Mitchell, Thomas M.
Abstract: Crack damage leading to failure in rocks can be accumulated through cyclic stressing in the crust. However, the vast majority of experimental studies to investigate cyclic stressing apply conventional triaxial stress states ( σ 1  >  σ 2  =  σ 3 ), while in nature the state of stress in the crust is generally truly triaxial ( σ 1  >  σ 2  >  σ 3 ). Furthermore, the magnitude of these crustal stresses can vary over time and their orientations can also rotate over time, generating multiple crack populations and bulk anisotropic crack damage. We investigate the evolution of crack damage under both conventional and true triaxial stress conditions by sequentially and cyclically varying stresses in all three principal directions on cubic samples of dry sandstone using independently controlled stress paths. We have measured, simultaneously with stress, the bulk acoustic emission output, as a proxy for crack damage. We report a directionally controlled crack damage memory effect which has implications for the approach to failure in complex tectonic stress environments. Plain Language Summary: Fractures that lead to failure and faulting in rocks accumulate over time with increasing amounts of stress. While a considerable amount of research has been devoted to understanding how cyclic stresses lead to the development of crack damage, very little work has considered how this damage evolves with direction. The lack of work on this topic is partly due to the type of experimental apparatus required to conduct suitable tests. In order to replicate multiple populations of crack damage in different directions, a true triaxial loading apparatus is needed. Such an apparatus replicates the general state of stress in the crust and allows those stresses to be varied with direction. It is well known that the stress field around fault zones, in volcanoes, and in geothermal systems can be complex and can rotate over time. By conducting experiments using a novel true triaxial apparatus we find a directionally controlled crack damage memory effect which has implications for the approach to failure of critically stressed rocks in complex tectonic stress environments. As such, these experimental results will be of interest to those studying fault zones and volcanic processes. Key Points: Damage onset depends only on the level of differential stress in any direction and so occurs at the same point regardless of the direction that σ1 is applied However, the magnitude of damage also depends on the level of σ2 in any direction, and so materials that are cyclically stressed may exhibit different damage levels in different directions Damage states not only depend on the individual stress state but also on the stress history